Structural integrity and life assessment of rotating equipment. (July 2020) - Milovanović, N.; Sedmak, A.; Arsic, M.; Sedmak, S.A.; Božić, Ž.
Highlights: Numerical analysis of behaviour of a turbine shaft, based on experimental results. Static and fatigue simulations, using regular and extended finite element method. Remaining life assessment of turbines with long cracks. Abstract: Failures of rotating equipment often cause severe consequences, so it is necessary to study their integrity and life as detailed as possible, especially when crack is detected. In the case studied here, hydro power plant turbine shaft is analysed by using fracture mechanics parameters both for static and dynamic loading in order to assess its structural integrity and life. In both cases classical engineering approach and Finite Element Method have been applied to evaluate stress state and number of cycles from a given initial crack length to its critical value. Results of analytical and numerical modelling are compared to verify both approaches.